Geometric Characteristics And Sedimentation Analysis Of Urban Drainage Channels In Alumunium Raya - Sinaga, Tiur Sari Tua; Jaya, Ardino Wira; Simanjuntak, Rizky; Prayogo, Wisnu; Harahap, Rumilla (CV. SINAR HOWUHOWU, 2026)
Urban drainage systems are crucial for managing surface runoff and preventing flooding in densely populated areas like Medan. However, rapid urbanization, population growth, and sedimentary layers often reduce the hydraulic capacity of these channels, which can lead to local flooding. The purpose of this study was to examine the geometric characteristics and sedimentation conditions of the drainage channels on Jalan Alumunium Raya Medan. This study used a descriptive-evaluative method that combined field surveys for primary data on nine observation segments with secondary data analysis in the form of rainfall and population statistics. The study found significant sedimentation with a height of up to 0.8 m, reducing the effective capacity of the channel.Geometric measurements indicate that the channel is between 1.0 and 1.55 meters wide and 0.45 and 1.4 meters deep. Analysis indicates that the projected population of 37,050 by 2025 and high annual rainfall (2,100–2,600 mm) both increase the amount of runoff the system must handle. The total sediment volume is 1,359.23 m³, and the flow rate is 1.94 m³/s. In conclusion, the current drainage system is not functioning properly and can cause flooding. To restore the effective capacity of the channel and ensure long-term urban water management, regular maintenance, sediment dredging, and normalization of the channel dimensions are essential.